A novel approach based on low‐field NMR for the detection of the pathological components of sputum in cystic fibrosis patients. Issue 4 (22nd August 2017) - Abrami, Michela; Ascenzioni, Fiorentina; Di Domenico, Enea Gino; Maschio, Massimo; Ventura, Alessandro; Confalonieri, Marco; Di Gioia, Sante; Conese, Massimo; Dapas, Barbara; Grassi, Gabriele; Grassi, Mario
Abstract : Purpose: Development of a reliable, simple method to monitor lung condition in cystic fibrosis (CF) patients. Lung functionality assessment in CF patients is relevant, as most of them still die of respiratory failure. In lung mucus (sputum) of CF patients, components such as proteins, biopolymers, DNA, bacteria, and mucin are pathologically increased. As lung functionality is related to the amount of the pathological components in the sputum, their determination can help clinicians in monitoring lung condition and planning therapy. Methods: Low‐field NMR was used to evaluate the variation of the relaxation time (T2m ) of the water hydrogens present in CF sputum in relation to the amounts of the pathological components. Low‐field NMR was tested in artificial samples (mucin or alginates), then in conditional sputum (saliva from healthy volunteers, added by different amounts of the pathological components), and finally in 12 patients' sputums, in which T2m was correlated to a commonly used lung monitoring test (i.e., forced expiratory volume in the first second). Results: T2m significantly ( P  < 0.05) differed between samples with and without pathological components and between healthy and CF patients ( P  < 0.05), in which T2m correlated ( r  = 0.87) with FEV1 . Conclusions: The presented method can potentially become a valuable lung‐monitoring tool in CF patients. Magn Reson Med 79:2323–2331, 2018. © 2017 International Society for Magnetic Resonance in Medicine.